Cardiac energy harvesting and sensing based on piezoelectric and triboelectric designs. (October 2020) - Dong, Lin; Jin, Congran; Closson, Andrew B.; Trase, Ian; Richards, Haley C.; Chen, Zi; Zhang, John X.J.
Abstract: Cardiac implantable devices are effective both as methods of controlling irregular heartbeats in people with heart rhythm disorders and as interventional therapy for cardiac diseases. However, early failures and battery limitations of cardiac medical devices lead to periodic battery replacement surgeries for patients that are both risky and costly. Self-sustainable energy generation could significantly extend the lifetime and effectiveness of cardiac implantable devices and other implantable biomedical devices (IMDs). The human heart is a compelling in vivo energy source and is a natural battery to power IMDs. In this review, we discuss current trends of developing self-powered cardiac medical devices harvesting the energy from the heart. Based on key challenges and limitations, we propose design principles for cardiac energy harvesters and sensors. We further discuss advanced energy materials, structural and fabrication considerations, biosafety and biocompatibility, and comfortability and flexibility. Moreover, recent advances in cardiac energy harvesting and sensing devices in both in vivo and in vitro studies are reviewed and discussed. Such sustainable energy strategies based on piezoelectric and triboelectric designs provide a promising means to reduce the reliance on batteries for powering cardiac medical devices and other IMDs. Graphical abstract: Image 1 Highlights: Self-sustainable energy generation significantly extends the lifetime and effectiveness of implantable biomedical devices. The design principles for cardiac energy harvesters and sensors are proposed. The review is focused on sustainable energy strategies on piezoelectric and triboelectric designs. Recent progress with summaries of devices performance are discussed along with future perspectives in the field.